Education policy and its impact on socioeconomic outcomes in Northern Nigeria: A sustainable development perspective - Micheal Godwin Okoliko; Abdulhafeez Adebayo (Journal of Education, Social & Communication Studies, 2025)
This paper examines the impact of education policy on socioeconomic outcomes in Northern Nigeria through the lens of sustainable development. Focusing on the alignment of these policies with the Sustainable Development Goals (SDGs), particularly SDG 4 (Quality Education), the study explores how efforts to improve access, quality, and equity in education contribute to broader regional development. The study concludes that education plays a critical role in reducing poverty (SDG 1: No Poverty) and promoting gender equality (SDG 5: Gender Equality), emphasizing the urgent need for inclusive educational policies that bridge regional disparities. Despite progress, challenges such as inadequate funding, infrastructure deficits, and cultural barriers continue to hinder the full achievement of these goals. Utilizing human capital theory, the study analyzes how investment in education enhances individuals’ productivity and economic potential, fostering long-term socioeconomic growth. Hence, the study recommends that government bodies, NGOs, and communities collaborate to address these challenges and ensure the sustainability of educational reforms in Northern Nigeria.